Shipwreck on the Pirate Islands - Stilton, Geronimo; Fontina, Mary; Stracchino, Johnny; Edizioni Piemme (New York : Scholastic, 2005)
Geronimo Stilton embarks on an adventure to investigate rumors of a haunted pirate treasure buried on a desert island.
"#18"--Spine.
Translation of: L'isola del tesoro fantasma.
3.5
3-6.
3-6
Keywords: Stilton, Geronimo -- Fiction; Stilton, Geronimo -- Fiction; Islands -- Juvenile fiction; Journalists -- Juvenile fiction; Mice -- Juvenile fiction; Treasure troves -- Juvenile fiction; Buried treasure -- Fiction; Islands -- Fiction; Journalists -- Fiction; Mice -- Fiction; Buried treasure -- Fiction; Islands -- Fiction; Journalists -- Fiction; Mice -- Fiction; Action and adventure fiction; Detective and mystery fiction